Muzyczne wyzwolenie z języka? Filozoficzne aspekty muzycznych inspiracji w poezji Mirona Białoszewskiego - Bochyńska, Agata (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2012)
Miron Bialoszewski is known for his untypical and idiosyncratic language of his poetry, as well as prose and drama that he has created. However, it is possible to find many connections between those linguistic experiments and the strategies used by polish avant-garde poets during the interwar years. It makes the works of Bialoszewski both innovative and dependent on the history of literature. Through the analysis of his specific language and the content of his poetry, as well as the comparison to the works and statements of the polish avant-garde representatives, author of this paper tries to recreate the philosophical backgroud of Bialoszewski's poems and explain how is the concept of music present in them. The article is divided into two main parts. The first main problem is a question about the philosophical condition of the language that we can encounter in this poetry — are we free in using our language or maybe we are limited by the word? The negative response to the first question leads to the necessity of possible solu-tions. Here music appears. It seems to be for Bialoszewski as the possibility of escaping from the limitations of the language. At the same time, music in his poetry is a new way of describing the world and a form of expressing ones thoughts.